(3ddJHGjf GdGbdjej aj eSJhjGJ GdHWGdI h eYOdGJgG aj GdCQOfs - (3jhfS SGde YHO GdZfj(B, (3GdWQGhfIs ((3YeGf(B:s (3OGQ cfhR GdeYQaI(B,s, 2009)
(3deMI Yf XGgQI GdHWGdI h OQGSJgG , JMOjO CKQ eLehYGJ eNJdaI ef GdeJZjQGJ GdNGUI HGdeJYWdjf Yf GdYed , cGdeJZjQGJ GdOjehZQGajI h GdGbJUGOjI h GdGLJeGYjI Ydi JHGjf eSJhjGJ GdHWGdI h eYOdGJgGYdi GdeSJhi GdeMdj (B( (3GdeMGaXGJ (B) (3h GdGbdjej Ydi eSJhi GdCQOf (B.s
(3eQGLY U(B.255 (3; edGMb U(B.261 (3; GTcGd U(B.12 (3;NQGFW U(B.13 (3; LOGhd U(B.14s
Keywords: (3GdGMUGA GdhUajs; (3GdHWGdI(B- (3GdGQOfs; (3GdJMdjd GdGMUGFjs